Analisis Penyerapan Tenaga Kerja Pada Sektor Unggulan di Kabupaten Pasuruan - Arvan Pradita Ibrahim; Ririt Iriani; Riko Setya Wijaya (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
The potential and economic superiority in each region can be a source for economic growth. The advantages of economic sectors in the region can be a tool of economic growth and can be an important factor in creating new business fields so that they are able to absorb labor in the area. One of the initiators of high economic growth in one area is marked by the level of GDRP in the area. This research aims to identify the leading sector located in Pasuruan Regency as well as its relationship with labor absorption and also compare the absorption of labor in the leading sector and non-seeded sector. This type of data used in this study is secondary data in the period 2010 to 2019 and is processed using location quotient (LQ), simple linear regression and shift share. Based on the results of research, the leading sector in Pasuruan Regency is the processing industry sector; electricity, gas, and clean water sectors; The construction sector has a positive and significant effect on the absorption of labor, while the remaining 6 sectors fall into the non-flagship sector, namely, Agriculture; Mining, and Excavation; Trade, Hotels and Restaurants; Transportation and Communication; Finance, Rentals, Corporate Services; Services negatively and significantly affect the absorption of labor.